KEBAN GALERİ SUYUNDA LEMNA GİBBA VE LEMNA MİNOR KULLANILARAK AG VE MN'IN GİDERİLMESİ - DEMİR, HATİCE KÜBRA (Fırat Üniveristesi, 2017)
Bu çalışmada, Lemna gibba ve Lemna minor bitkilerinin galeri çıkış suyundaki Ag ve Mn giderim kapasiteleri incelenmiştir. Bu amaçla Lemna gibba ve Lemna minor bitkileri galeri çıkış suyuna yerleştirilen ve kesintisiz olarak beslenen reaktörlere adapte edilmiştir. Çalışma süresince (8 gün) günlük alınan su örneklerinde sıcaklık, pH ve elektrik kondüktivite değerleri (EC) anlık olarak ölçülmüş, bitkiler ise yıkanmış, kurutulmuş ve 300 oC' de etüvde 24 saat süre ile yakılmıştır. Kül örneklerindeki Ag ve Mn miktarları Acme (Kanada) analiz laboratuvarında ICP-MS ile analiz edilmiştir. Analiz sonuçlarına göre elde edilen veriler şöyledir: Ag için L.gibba 2. günde % 11439, L.minor ise 2. günde % 4770; Mn için L.gibba I. günde % 200, L.minor ise 2. günde % 155 gibi akümülasyon performansı göstermiştir. Ayrıca bu bitkilerin en ideal hasat zamanlarında ise L.gibba 5262 lt, L.minor ise 4484 lt sudan Ag gidermiştir. Aynı zamanda, L.gibba deneyin ilk gününde 185 lt, L.minor ise deneyin ikinci gününde 2190 lt sudan Mn akümüle etmiştir Anahtar Kelimeler: Akümülasyon, Lemna gibba, Lemna minor, ağır metal, galeri suyu, Keban

In this study, Ag and Mn removal efficiencies of Lemna gibba and Lemna minor plants in the gallery water were investigated. For this aim, Lemna gibba and Lemna minor plants were placed in the gallery water of Keban Pb-Zn ore deposits and adapted individually fed to the reactors. During the study period (8 days), the temperature, pH and electric conductivity values (EC) of the gallery water were daily measured in real time. These plants were washed, dried and burred at 300 oC' for 24 hours in drying oven. Then, these ash samples were send to Acme (Canada) analysis laboratory for the determination of amounts of Ag and Mn and analyzed by ICP-MS. According to the results of analysis the obtained efficiencies are as follows; % 11439 at day 2 and % 4770 at day 2 for Ag in Lemna gibba and Lemna minor, respectively, % 200 at day 1 and % 155 at day 2 for Mn in Lemna gibba and Lemna minor, respectively. Moreover, at the ideal harvesting times of these plants, Ag in 5262 lt and 4484 lt water were accumulated by L. gibba and L. minör. At the same time, L. gibba on the first day and L. minor on the second day accumulated Mn in 185 liters and 2190 liters of the gallery water, respectively. Key words: Accumulation, Lemna gibba, Lemna minor, heavy metals, gallery water, Keban
The removal of Ag and Mn by Lemna gibba and Lemna minor in the Keban gallery water
Keywords: Jeoloji Mühendisliği